Urban Sprawl and Urbanization Companies the Work of the Compañía Madrileña de Urbanización, the Garden City Pioneer Company, the First Garden City Ltd and the Cía. City - Pescatori, Carolina (Articles City, História and Culture, 2020)
This article problematizes the contemporary phenomenon of urban sprawl within the field of Urbanism history through a historiography of the performance of urbanization companies with recognized importance in the history of Urbanism: the Compañía Madrileña de Urbanización, an urbanization company founded by Arturo Soria y Mata in order to implement his idea of a Linear City; the Garden City Pioneer Company and the First Garden City Ltd, founded, respectively, to raise funds and manage the construction of Letchworth, in England, the first built city garden, whose theoretical scheme Ebenezer Howard conceived in 1889; and the City of São Paulo Improvements and Freehold Company Ltd, which implemented the first garden suburbs in São Paulo. The narrative on each company highlights two aspects: how the urban concepts propagated by these companies relate to the idea of urban sprawl and which business strategies were developed to enable dispersion-related ventures.